Preparation method of high-performance plant fiber composite material for automotive trim
By reinforcing the plant fiber material and resin composite, high-performance plant fiber composite materials are prepared, which solves the problems of insufficient mechanical properties and safety of existing materials in automotive interior applications, and achieves mechanical properties comparable to traditional fiber composite materials and lower manufacturing costs.
Patent Information
- Application Number
- CN202411370030.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Existing plant fiber composite materials have problems such as insufficient bending performance, poor toughness and low hardness in automotive interior applications, which limits their application scope. At the same time, the volatility of formaldehyde in its matrix poses a potential threat to human health.
High-performance plant fiber composite materials were prepared by enhancing treatment, quasi-isotropic treatment and resin composite treatment. Specific steps include: configuration of the treatment solution, de-hemicellulose treatment, vacuum impregnation, hot press forming, resin composite and blank curing.
It achieves a balance of high strength, high hardness and high toughness, and its mechanical properties are close to traditional carbon fiber and glass fiber composite materials, while reducing the use of chemical substances and improving the safety and cost-effectiveness of the material.
Smart Images

Figure CN119898107A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to a method for preparing a high-performance plant fiber composite material for automobile interior decoration. Background Art
[0002] At present, in the field of automotive interior, plant fibers are usually used as a reinforcing phase to improve the bending strength and toughness of composite materials, such as: using hemp fiber and PET / PP composite to prepare car roofs; using bamboo fiber and resin mixed and molded into car door linings, etc. However, compared with composite materials such as carbon fiber and glass fiber, natural fiber composite materials still have problems such as insufficient bending performance, poor toughness, and low hardness in automotive interior materials, which greatly limits the application scope of plant fiber composite materials. In order to solve the above problems, it is often difficult to achieve a balance of mechanical properties by increasing the fiber volume fraction and other solutions.
[0003] On the other hand, plant fiber composite materials have become an ideal substitute for traditional automotive interior materials such as carbon fiber boards, glass fiber boards, and plastic boards due to their sustainability, low cost, sound insulation, sound insulation, and damping properties. However, the matrix of plant fiber composite materials is still plastic, which inevitably causes the volatilization of harmful gases such as formaldehyde. In the confined and narrow space of the car, these volatiles can cause potential harm to the human body. In order to avoid this harm, the use of formaldehyde-free composite materials will also increase the manufacturing cost of the car.
[0004] Therefore, it is urgent to develop a method for preparing plant fiber composite materials that have high strength, high hardness, high toughness, low cost, and are simple and easy to use. This is an exploration of how plant fiber composite materials can fully replace carbon fiber, glass fiber and other automotive interior materials, and a breakthrough in all-plant fiber-based automotive interiors, with huge market potential. Summary of the invention
[0005] The purpose of the present invention is to design a method for preparing a high-performance plant fiber composite material for automobile interior, which has the properties of high strength, high hardness and high toughness, can be comparable to organic / inorganic fiber composite materials such as carbon fiber and glass fiber for traditional automobile interior, and also has the advantages of low cost and simple process.
[0006] To this end, a method for preparing a high-performance plant fiber composite material for automobile interior decoration of the present invention comprises the following steps: (1) Preparation of treatment solution: Weigh 0.1-10 g of hydroxypropyl cellulose and 0.5-40 g of cellulose nanocrystals respectively, mix them, add water, and prepare 100 mL of treatment solution; (2) Weigh a certain amount of air-dried plant fiber material with a moisture content of less than 10%, place it in a potassium hydroxide aqueous solution with a mass fraction of 0.1% to 20%, heat treat it in water at 90°C for 1 to 36 hours, take it out and drain off the water to obtain a dehemicellulose plant material; (3) placing the dehemicellulose plant material in the treatment solution and vacuum impregnating it at -0.095 MPa for 10 min to obtain a treated plant fiber material; (4) taking out the treated plant fiber material, controlling the moisture content to 30%, and hot pressing at 60 to 170° C. and 1 to 25 MPa for 0.1 to 24 h to obtain a reinforced plant fiber sheet; (5) stacking the reinforced plant fiber sheets, coating the stacked surfaces with resin, and performing quasi-isotropic assembly and isotropic cross assembly according to the staggered seams of adjacent layers; (6) Placing the assembled material in a mold and curing it at 4 MPa and 80° C. for 1 to 6 h to obtain a high-performance plant fiber composite material.
[0007] As a further description of the above technical solution: the plant fiber material is wood, bamboo, hemp, straw or grass, and the thickness of the wood or bamboo is a single board of 0.1 to 5 mm; Hemp, straw or grass plants are first cut longitudinally into strip fiber materials with a diameter of 0.5 to 3 mm by a cutting machine, and then formed into woven sheets by a weaving method.
[0008] As a further description of the above technical solution: the treatment solution is a mixed aqueous solution of hydroxypropyl cellulose and cellulose nanocrystals, with mass fractions of 0.1% to 10% and 0.5% to 40% respectively.
[0009] As a further description of the above technical solution: the same type of blanks are blanks of the same type of materials; The wood and bamboo materials include single-layer blanks and multi-layer blanks. A single-layer blank is a blank in which the same layer of wood or bamboo boards has the same thickness, the same layer is arranged side by side with width, and the longitudinal end to end is connected with length, and the longitudinal end to end connection seam is flat-jointed; a multi-layer blank is a blank in which multiple layers of wood or bamboo boards are staggered up and down, the same layer of wood or bamboo boards has the same thickness, the upper and lower adjacent layers are alternately arranged and the same-direction seams are staggered, the upper and lower adjacent layers are staggered with longitudinal grains at 20° to 90°, and the number of layers is odd and at least 3; Hemp, straw or grass plants include single-layer assemblies and multi-layer assemblies. A single-layer assembly is a woven sheet formed by first layers being butt-jointed and staggered, and warp and weft being cross-woven to be widened and lengthened; a multi-layer assembly is an assembly of at least three layers of woven sheets stacked up and down, and the woven sheets on the same layer have the same thickness.
[0010] As a further description of the above technical solution: the cross-assembly of same and different types is an alternating stacking of the same layer of the same type of material and the adjacent layer of another type of material; the same type of material is a layer of wood sheets or bamboo sheets, and the other type of material is one or more layers of woven sheets of hemp, straw or grass plants, and the assembly form is: (1) Three-layer assembly form: wood sheets, one or more layers of woven sheets, wood sheets; or bamboo sheets, one or more layers of woven sheets, bamboo sheets; or wood sheets, one or more layers of woven sheets, bamboo sheets; or bamboo sheets, one or more layers of woven sheets, wood sheets; wherein the longitudinal grains of two wood sheets, or two bamboo sheets, or two bamboo-wood sheets are staggered at 20° to 90°; or one or more layers of woven sheets, wood sheets or bamboo sheets, one or more layers of woven sheets; (2) The multi-layer odd-number blank is a blank in which a layer of wood sheet or a layer of bamboo sheet is alternately stacked with one or more layers of woven sheet, wherein the longitudinal grains of two adjacent wood sheets, or two bamboo sheets, or two bamboo-wood sheets are staggered at 20° to 90°; or a composite blank in which one or more layers of woven sheets are alternately stacked with a layer of wood sheet or a layer of bamboo sheet; As a further description of the above technical solution: the resin is a composite resin, which can be epoxy resin, phenolic resin, urea-formaldehyde resin, polylactic acid, or PP.
[0011] As a further description of the above technical solution: the moisture content of the assembly material is 10-12%.
[0012] The present invention has the following beneficial effects: 1. The present invention sequentially performs a reinforcement treatment, a quasi-isotropic treatment and a resin composite treatment on the plant fiber material, and finally obtains a high-performance plant fiber composite material for automobile interior. This composite material has mechanical properties that surpass those of traditional plant fiber composite structural parts and achieves a balance of high strength, high hardness and high toughness. The mechanical properties of the plant fiber composite material prepared by the present invention are comparable to those of traditional organic / inorganic fiber composite materials such as carbon fiber and glass fiber for automobile interior. Comparative tests show that the high-performance plant fiber composite material for automobile interior prepared by the present invention has a flexural strength of 111.18 to 239.22 MPa, a Shore hardness of 76.5 to 80.5, and a toughness of 5.5 to 9.6 MJ / cm 3 The flexural strength of carbon fiber composite materials for automotive interiors of the same weight and thickness is 193.70MPa, the Shore hardness is 80.0, and the toughness is 6.4MJ / cm 3 The bending strength of the glass fiber composite material for automobile interior with the same weight and thickness is 193.70MPa, the Shore hardness is 80.0, and the toughness is 6.4MJ / cm 3The bending strength of the bamboo fiber composite material for automobile interior with the same weight and thickness is 79.39MPa, the Shore hardness is 78.0, and the toughness is 1.3MJ / cm 3 .
[0013] The above index data indicate that the high-strength plant fiber composite board for automobile interior prepared by the method of the present invention has high bending strength, high hardness and high toughness that surpass traditional plant fiber composite boards, and has mechanical properties comparable to carbon fiber and glass fiber composite boards for automobile interior, providing a new solution for creating lightweight, high-performance and full-coverage automobile interior components.
[0014] 2. The plant fiber composite material for automobile interior prepared by the present invention greatly reduces the additional chemical substances required for chemical fiber compounding, realizes high-toughness and high-strength materials based on plant fibers, reduces the amount of chemical fibers used, and provides a method for promoting the application of plant waste.
[0015] 3. The preparation method of the present invention solves the problem that the current plant fiber composite materials are not sufficient to replace all automobile interior materials, and broadens the application of plant fiber composite materials in the field of automobile interior. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic diagram of the three-layer assembly structure of the present invention; Figure 2 Another schematic diagram of the structure of the three-layer assembly of the present invention; Figure 3 It is a schematic diagram of the 5-layer assembly structure of the present invention; Figure 4 This is a schematic diagram of a layer of bamboo sheet material spliced in width and length according to the present invention; Figure 5 It is a schematic diagram of the stamping structure of the blank assembly of the present invention. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described in conjunction with specific embodiments below, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without creative work all belong to the protection scope of the present invention. The construction methods in the following embodiments, unless otherwise specified, are all conventional methods. The materials, devices, equipment, etc. used in the following embodiments, unless otherwise specified, can all be obtained from commercial channels.
[0018] Example 1: Figures 1 to 5As shown, a method for preparing a high-performance plant fiber composite material for automobile interior decoration comprises the following steps: (1) Weigh 0.5 g of hydroxypropyl cellulose and 1 g of cellulose nanocrystals, mix them, and add water to prepare 100 mL of treatment solution.
[0019] (2) A certain amount of air-dried bamboo chips with a thickness of 2 mm were weighed and hydrothermally treated with a 2% by mass potassium hydroxide aqueous solution at 90°C for 2 h. The solution was then drained off and the bamboo chips were placed in the treatment solution and vacuum immersed for 10 min at -0.095 MPa.
[0020] (3) The bamboo sheet is taken out, the moisture content is controlled at 30%, and then hot pressed at 140° C. and 8 MPa for 0.5 h to obtain a reinforced bamboo sheet.
[0021] like Figure 4 As shown, (4) the butt joint surfaces of several pieces of reinforced bamboo sheets are coated with epoxy resin to form a layer of blanks, wherein the thickness of a layer of bamboo sheets 2 is the same, the same layer is parallelly connected in width, and the longitudinal end-to-end connection is connected in length, and the longitudinal end-to-end connection seams 21 are flat-joined to form a layer of bamboo sheet 2. Three pieces of bamboo sheets are taken to be stacked and assembled, the thickness of the same layer of bamboo sheets is the same, the upper and lower adjacent layers are alternately arranged and the same-direction seams are staggered, and the longitudinal grains of the upper and lower adjacent layers are staggered at 90 degrees to form a three-layer bamboo sheet blank material, and the butt joint surfaces of each layer of bamboo sheets are coated with epoxy resin, and the moisture content of the blank material is 10%.
[0022] (5) The assembled material 6 is placed in a mold and cured at 4 MPa and 80° C. for 1 h to obtain a high-performance plant fiber composite material.
[0023] like Figure 5 As shown, the mold includes an upper punch 4 and a lower die 5, and the assembly material 6 is placed on the upper end of the lower die. The pressure is perpendicular to the assembly material and transmitted to the upper punch 4. The upper punch 4 moves downward to press the assembly material into the lower die 5, and is cured at 4MPa and 80°C for 1h to obtain a high-performance plant fiber composite material formed in one step, which is then trimmed to form a product.
[0024] After testing, the sample obtained in Example 1 has a bending strength of 239.22 MPa, a Shore hardness of 78.5, and a toughness of 9.6 MJ / cm 3 .
[0025] Embodiment 2: A method for preparing a high-performance plant fiber composite material for automobile interior, comprising the following steps: Weigh 0.2g of hydroxypropyl cellulose and 0.5g of cellulose nanocrystals respectively, mix and add water to prepare 100mL of treatment solution. Weigh a certain amount of 2mm thick forged wood chips, treat them hydrothermally in a 2% potassium hydroxide aqueous solution at 90℃ for 1h, drain the solution, place the forged wood chips in the treatment solution, and vacuum impregnate them at -0.095MPa for 10min. Take out the forged wood chips, control the moisture content at 30%, and then hot press them at 80℃ and 20MPa for 12h to obtain enhanced forged wood chips. Coat the butt surfaces of several enhanced forged wood chips with epoxy resin for a layer of assembly. A layer of assembly is a layer of forged wood chips 1 with the same thickness, and the same layer is connected side by side in width, and the longitudinal end to end is connected in length. The longitudinal end to end joint seam is flat-jointed to form a layer of forged wood chips. Take 3 pieces of one-layer forged wood chips and stack them for assembly. The thickness of the same layer of forged wood chips is the same. The upper and lower adjacent layers are arranged alternately and the same-direction seams are staggered. The longitudinal grains of the upper and lower adjacent layers are staggered at 70° to form a three-layer forged wood chip assembly. The butt joints of each layer of forged wood chips are coated with epoxy resin. The moisture content of the assembly is 10%. The assembled assembly is placed in a mold and cured at 4MPa and 80℃ for 2h to obtain a high-performance plant fiber composite material.
[0026] After testing, the sample obtained in Example 2 has a bending strength of 193.46 MPa, a Shore hardness of 80.5, and a toughness of 5.5 MJ / cm 3 .
[0027] Example 3: The difference from Example 1 is that: a certain amount of fiber material cut longitudinally into strips with a diameter of 1 to 3 mm by a cutting machine is weighed, and air-dried wheat straw strip fibers are woven into a woven sheet, and placed in a 2% potassium hydroxide aqueous solution, hydrothermally treated at 90°C for 1 hour, the liquid is drained, and the woven sheet is placed in the treatment solution, and vacuum impregnated for 10 minutes at -0.095MPa. The above woven sheet is taken out, and after the moisture content is controlled at 30%, it is hot-pressed at 80°C and 20MPa for 12 hours to obtain a reinforced woven sheet, and three layers of woven sheets are stacked and assembled, and the assembled straw is placed in a mold, and cured at 4MPa and 80°C for 1 hour to obtain a high-performance plant fiber composite material.
[0028] After testing, the sample obtained in Example 3 has a bending strength of 119.27 MPa, a Shore hardness of 77.5, and a toughness of 6.8 MJ / cm 3 .
[0029] Example 4: The difference from Example 1 is that a certain amount of air-dried Pennisetum is weighed and woven into a 3cm×3cm straw mat, and the straw mat is placed in a 2% potassium hydroxide aqueous solution, the solution is heated to 90°C, and hydrothermally treated for 1h, and then the liquid is drained, and the straw mat is placed in the treatment solution, and vacuum impregnated for 10min at -0.095MPa. The above straw mat is taken out, and after the moisture content is controlled at 30%, it is hot pressed at 80°C and 20MPa for 12h to obtain a reinforced straw mat 3, and the three layers of straw mats are stacked and assembled, and each stacked adhesive surface is coated with phenolic resin, and the assembled straw mat is placed in a mold, and cured at 4MPa and 80°C for 1h to obtain a high-performance plant fiber composite material.
[0030] After testing, the sample obtained in Example 4 has a bending strength of 111.18 MPa, a Shore hardness of 76.5, and a toughness of 7.6 MJ / cm 3 .
[0031] Example 5: Figure 1 As shown, the reinforced forged wood sheets obtained in Example 2 and the reinforced straw mats obtained in Example 4 were assembled into a three-layer structure, forming a three-layer structure of a layer of wood sheet 1, two layers of woven sheets 3, and a layer of wood sheet. The longitudinal grains of the two layers of wood sheets were staggered at 90°, and the butt joints of the layers were coated with epoxy resin. The moisture content of the assembled material was 12%. The assembled material was placed in a mold and cured at 4MPa and 80°C for 2h to obtain a high-performance plant fiber composite material.
[0032] After testing, the sample obtained in Example 5 has a bending strength of 190.5 MPa, a Shore hardness of 79.5, and a toughness of 5.1 MJ / cm 3 .
[0033] Example 6: Figure 2 As shown, the reinforced bamboo sheet 2 obtained in Example 1, the reinforced forged wood sheet obtained in Example 2, and the reinforced straw mat obtained in Example 4 are assembled into a three-layer structure to form a three-layer structure of a layer of wood sheet 1, two layers of woven sheet 3, and a layer of bamboo sheet 1. The longitudinal grains of the wood sheet and the longitudinal grains of the bamboo sheet are staggered at 90°. The butt joints of each layer are coated with epoxy resin, and the moisture content of the assembled material is 11%. The assembled material is placed in a mold and cured at 4MPa and 80°C for 2h to obtain a high-performance plant fiber composite material.
[0034] After testing, the sample obtained in Example 6 has a bending strength of 230.6 MPa, a Shore hardness of 74.1, and a toughness of 8.1 MJ / cm 3 .
[0035] Example 7: Figure 2As shown, the reinforced bamboo sheet 2 obtained in Example 1, the reinforced forged wood sheet obtained in Example 2, and the reinforced straw mat obtained in Example 4 are assembled into a 5-layer structure, forming a 5-layer structure assembly of a layer of wood sheet 1, 2 layers of woven sheets 3, a layer of bamboo sheet 2, 2 layers of woven sheets 3, and a layer of wood sheet 1. The longitudinal grains of the adjacent wood sheets and the longitudinal grains of the bamboo sheets are staggered at 90°. The butt joints of the layers are coated with epoxy resin, and the moisture content of the assembled material is 10%. The assembled material is placed in a mold and cured at 4MPa and 80°C for 2h to obtain a high-performance plant fiber composite material.
[0036] Comparative Example 1: The preparation of the comparative example of carbon fiber composite material for automobile interior comprises the following steps: coating the purchased carbon fiber woven cloth with epoxy resin on both sides, and performing quasi-isotropic assembly in the manner of Example 1. The assembled carbon fiber cloth is placed in a mold, and cured at 1 MPa and 80° C. for 1 h to obtain a carbon fiber composite material comparative sample.
[0037] After testing, the sample obtained in comparative example 1 has a bending strength of 83.78 MPa, a Shore hardness of 79.5, and a toughness of 4.9 MJ / cm 3 .
[0038] Comparative Example 2: Preparation of a comparative example of a glass fiber composite material for automobile interior, comprising the following steps: coating the purchased glass fiber woven cloth with epoxy resin on both sides, and performing quasi-isotropic assembly in the manner of Example 1. The assembled carbon fiber cloth is placed in a mold, and cured at 1 MPa and 80° C. for 1 h to obtain a carbon fiber composite material comparative sample.
[0039] After testing, the sample obtained in comparative example 2 has a bending strength of 193.70 MPa, a Shore hardness of 80.0, and a toughness of 6.4 MJ / cm 3 .
[0040] Comparative Example 3: The preparation of the comparative example of bamboo fiber composite material for automobile interior decoration includes the following steps: fully mixing bamboo fiber and epoxy resin. Placing the above bamboo fiber in a mold, curing at 1 MPa and 80° C. for 1 h, and obtaining a comparative sample of ordinary bamboo fiber composite material.
[0041] After testing, the sample obtained in comparative example 3 has a bending strength of 79.39 MPa, a Shore hardness of 78.0, and a toughness of 1.3 MJ / cm 3 .
[0042] Test comparison table 1:
[0043] The index data of the above test comparisons indicate that the high-strength plant fiber composite board for automobile interior prepared by the method of the present invention has high bending strength, high hardness and high toughness that surpass traditional plant fiber composite boards, and has mechanical properties comparable to carbon fiber and glass fiber composite boards for automobile interiors, providing a new solution for creating automobile interior components that utilize less chemical fibers and plant fibers, turn waste into treasure, and are lightweight, high-performance and fully covered.
[0044] What is described above is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a high-performance plant fiber composite material for automobile interior, characterized in that: The steps include: (1) Preparation of treatment solution: Weigh 0.1-10 g of hydroxypropyl cellulose and 0.5-40 g of cellulose nanocrystals respectively, mix them, add water, and prepare 100 mL of treatment solution; (2) Weigh a certain amount of air-dried plant fiber material with a moisture content of less than 10%, place it in a potassium hydroxide aqueous solution with a mass fraction of 0.1% to 20%, heat treat it in water at 90°C for 1 to 36 hours, take it out and drain off the water to obtain a dehemicellulose plant material; (3) placing the dehemicellulose plant material in the treatment solution and vacuum impregnating it at -0.095 MPa for 10 min to obtain a treated plant fiber material; (4) taking out the treated plant fiber material, controlling the moisture content to 30%, and hot pressing at 60 to 170° C. and 1 to 25 MPa for 0.1 to 24 h to obtain a reinforced plant fiber sheet; (5) stacking the reinforced plant fiber sheets, coating the stacked surfaces with resin, and performing quasi-isotropic assembly and isotropic cross assembly according to the staggered seams of adjacent layers; (6) Placing the assembled material in a mold and curing it at 4 MPa and 80° C. for 1 to 6 h to obtain a high-performance plant fiber composite material.
2. A method for preparing a high-performance plant fiber composite material for automobile interior according to claim 1, characterized in that: The plant fiber material is wood, bamboo, hemp, straw or grass, and the thickness of the wood or bamboo is 0.1-5 mm single board; Hemp, straw or grass plants are first cut longitudinally into strip fiber materials with a diameter of 0.5 to 3 mm by a cutting machine, and then formed into woven sheets by a weaving method.
3. A method for preparing a high-performance plant fiber composite material for automobile interior according to claim 1, characterized in that: The treatment solution is a mixed aqueous solution of hydroxypropyl cellulose and cellulose nanocrystals, with mass fractions of 0.1% to 10% and 0.5% to 40% respectively.
4. A method for preparing a high-performance plant fiber composite material for automobile interior according to claim 1, characterized in that: The same type of blanks are made of the same type of materials. The wood and bamboo materials include single-layer blanks and multi-layer blanks. A single-layer blank is a blank in which the same layer of wood or bamboo boards has the same thickness, the same layer is arranged side by side with width, and the longitudinal end to end is connected with length, and the longitudinal end to end connection seam is flat-jointed; a multi-layer blank is a blank in which multiple layers of wood or bamboo boards are staggered up and down, the same layer of wood or bamboo boards has the same thickness, the upper and lower adjacent layers are alternately arranged and the same-direction seams are staggered, the upper and lower adjacent layers are staggered with longitudinal grains at 20° to 90°, and the number of layers is odd and at least 3; Hemp, straw or grass plants include single-layer assemblies and multi-layer assemblies. A single-layer assembly is a woven sheet formed by first layers being butt-jointed and staggered, and warp and weft being cross-woven to be widened and lengthened; a multi-layer assembly is an assembly of at least three layers of woven sheets stacked up and down, and the woven sheets on the same layer have the same thickness.
5. A method for preparing a high-performance plant fiber composite material for automobile interior decoration according to claim 1, characterized in that: The cross-assembly of same and different types is an alternating stacking of the same layer of the same type of material and the adjacent layer of another type of material; the same type of material is a layer of wood sheets or bamboo sheets, and the other type of material is one or more layers of woven sheets of hemp, straw or grass plants. The assembly form is: (1) Three-layer assembly form: wood sheets, one or more layers of woven sheets, wood sheets; or bamboo sheets, one or more layers of woven sheets, bamboo sheets; or wood sheets, one or more layers of woven sheets, bamboo sheets; or bamboo sheets, one or more layers of woven sheets, wood sheets; wherein the longitudinal grains of two wood sheets, or two bamboo sheets, or two bamboo-wood sheets are staggered at 20° to 90°; or one or more layers of woven sheets, wood sheets or bamboo sheets, one or more layers of woven sheets; (2) The multi-layer odd-number blank is a blank in which a layer of wood sheet or a layer of bamboo sheet is alternately stacked with one or more layers of woven sheet, wherein the longitudinal grains of two adjacent wood sheets, or two bamboo sheets, or two bamboo-wood sheets are staggered at 20° to 90°; Or a composite blank in which one or more layers of woven sheets and a layer of wood sheet or a layer of bamboo sheet are alternately stacked.
6. A method for preparing a high-performance plant fiber composite material for automobile interior decoration according to claim 1, characterized in that: The resin is a composite resin, which may be epoxy resin, phenolic resin, urea-formaldehyde resin, polylactic acid, or PP.
7. A method for preparing a high-performance plant fiber composite material for automobile interior decoration according to claim 1, characterized in that: The moisture content of the assembly material is 10-12%.
Citation Information
Patent Citations
Preparation method for wood-bamboo reinforced resin composite material based on high-pressure densification
CN108772922A
Bamboo wood reinforcing and synergistic treatment method
CN110919804A
Manufacturing method and application of bamboo-wood composite glued material
CN115070885A
Modified plant fiber composite material for hard tissue repair and preparation method thereof
CN118236555A
Natural fiber polymer composite and eco-friendly lightweight base material for automotive interior
EP2881249A1